(untitled) (Jurnal Studi Inovasi Pemerintahan, 2025)
This study aims to examine the implementation of the smart governance concept in the Integrated District Administration Services (Pelayanan Administrasi Terpadu Kecamatan, or PATEN) in West Palu District, Palu City. Smart governance is a governance approach that utilizes information and communication technology to enhance effectiveness, efficiency, transparency, and public participation in service delivery. This research uses a descriptive qualitative method with data collection techniques including in-depth interviews, direct field observation, and document studies. The informants in this study consist of five individuals: the sub-district head (Camat), the sub-district secretary, the head of the staffing and general affairs sub-division, the head of the public service section, and a community representative. This study focuses on four main indicators of smart governance according to Novitasari, namely transparency, technology, human resources (HR), and participation. The results show that three out of the four indicators have been implemented fairly well—transparency, human resources, and community participation. Transparency is reflected in the openness of information related to service procedures, although it still follows conventional methods. Human resources have demonstrated basic capabilities in providing services but are not yet fully adaptive to technology. Community participation has begun to take shape through forums and service satisfaction surveys. However, the technology indicator has not been optimally implemented. The absence of digital systems or technology-based service applications is a major obstacle. This indicates that adaptation to digital developments remains low, hindering improvements in the quality and speed of service delivery. Therefore, enhancing the technological aspect should be prioritized in efforts to realize effective, efficient, and responsive public services based on smart governance.